Do School Exclusions and Attainment Outcomes Disproportionately Impact Minority Ethnic Pupils? Analysis of Pupil Characteristics, Segregation, and Outcomes in England - Stephen Gorard; Nadia Siddiqui; Beng Huat See; Yiyang Gao (Education Sciences)
Large-scale administrative datasets show disproportionate figures for attainment outcomes and school exclusions for pupils in some ethnic groups in England. This surface gap in attainment and school exclusion is concerning, and we consider whether ethnicity is really the driver here. In this paper, we present the findings on KS2 and KS4 attainment and exclusion outcomes for the cohorts in 2019, which are available from the National Pupil Database in England (with around 600,000 pupils per cohort). We present the outcomes and other characteristics for each ethnic category available. The analyses then modelled the attainment and exclusion outcomes via multivariate regression, in terms of individual pupil characteristics and school-level figures including school segregation by pupil ethnicity and disability. The predictors were entered in batches from pupil background, through prior attainment, and school-level measures, to individual ethnicity. The findings show that prior attainment and special needs/disability status are the main drivers of attainment at both KS2 and KS4. Individual pupil ethnicity did not help to explain either attainment or exclusions, over and above these other factors, and this finding largely corroborates the descriptive results. However, the factors related to school-level segregation by ethnicity, free school meal eligibility (FSM), and having English as an additional language (EAL) are somewhat relevant in predicting pupils’ permanent school exclusion at KS4. These findings have implications for admission policies that can reduce school segregation and interventions that can support disadvantaged pupils’ wider learning experiences.